Neuroendocrine carcinoid tumors of breast - Clinicopathologic study of six cases - Scigliano, Horácio M. (2022)
Primary carcinoid tumor of the breast is a very rare tumor which existence and histogenesis are still controversial. Ductal basal stem cells seem to be possible source.In Retrospective study of 243 invasive and in situ, ductal and lobular mammary carcinomas following strict criteria of selection, six carcinoids were identified. All of the patients were females, mean age of 43 years, disclosing palpable nodules into upper outer quadrants mainly from right breast. Axillary involvement and carcinoid syndrome were not detected. Mammography showed dense opacities with regular outlines. Fine needle aspiration cytology suggested lobular neoplastic cells in three cases, atypical lobular hyperplasia in one and non-specific mucin (probably mucoid carcinoma) in the rest. As stage II of disease modified radical mastectomy was performed in all of the cases. Gross appearance showed tumors with 29.8 mm in average size, solid aspect in four cases and cystic gelatinous in two with pushing margins. Microscopically, basaloid was the most frequent pattern, with extracelullar mucin in three cases upto 28%. Mitosis were not observed. Differential diagnosis included lobular carcinoma, coloid carcinoma and carcinoid breast metastasis. Follow-up data indicate absence of local spread distant metastasis or death upon a mean of 3.8 years. None of the patients received radio, chemo or hormone therapy. 'We propose that quadrantectomy and axillary lymph nodes dissection should be the first choice of treatment. Radical surgery would be reserved for a second time surgical approach.